Hydration of proteins and nucleic acids: Advances in experiment and theory. A review - Biedermannová, Lada; Schneider, Bohdan (Biochimica et biophysica acta, 2016)
BACKGROUND: Most biological processes involve water, and the interactions of biomolecules with water affect their structure, function and dynamics. SCOPE OF REVIEW: This review summarizes the current knowledge of protein and nucleic acid interactions with water, with a special focus on the biomolecular hydration layer. Recent developments in both experimental and computational methods that can be applied to the study of hydration structure and dynamics are reviewed, including software tools for the prediction and characterization of hydration layer properties. MAJOR CONCLUSIONS: In the last decade, important advances have been made in our understanding of the factors that determine how biomolecules and their aqueous environment influence each other. Both experimental and computational methods contributed to the gradually emerging consensus picture of biomolecular hydration. GENERAL SIGNIFICANCE: An improved knowledge of the structural and thermodynamic properties of the hydration layer will enable a detailed understanding of the various biological processes in which it is involved, with implications for a wide range of applications, including protein-structure prediction and structure-based drug design.
Keywords: simulace molekulární dynamiky; Proteins; Nucleic Acids; zvířata; Water; Molecular Dynamics Simulation; nukleové kyseliny; proteiny; voda; Animals